Comment on new estimates of single photon parameters for setellite-based QKD - Shamsul Shaari, Jesni (Elsevier, 2010)
I comment on the results claiming to be new estimates for single photon parameters for satellite-based QKD in [1] to be based on a critical error in simple algebraic manipulations and further argue how their work would be more sensible upon the relevant corrections. However, this sensibility is at the price of rendering their conclusion nonjustifiable.